Emotion Analysis of Ideological and Political Education Using a GRU Deep Neural Network - Shen, Shoucheng; Fan, Jinling (Frontiers in Psychology, 2022)
Studying the emotional attribute of ideological and political education theoretically is of great significance to the theoretical development of ideological and political education, to promote the development of human emotion, and solve social-emotional problems. This study studies the emotional analysis of ideological and political education integrating Gate Recurrent Unit (GRU) and attention mechanism. Said BERT characteristics, based on the good results achieved in the downstream network adopts two-way GRU helped with the attention mechanism of long-focus respectively to extract the ideological and political education and emotional analysis of the correlation information and global information, the two complementary advantages, after fusion model fully study of high-level semantic information, combining the neural network model can further improve the accuracy of emotional information, Finally, the validity and domain adaptability of the model are verified on several public fine-grained emotion analysis datasets.